Blends of native LDPE with post consumer reclaimed low density and / or linear low density polyethylene and methods thereof

By mixing native LDPE and recovering LDPE in a twin screw extruder with high shear melting mixing native LDPE and recycling LDPE, the composite LDPE polymer is prepared, which solves the problem of difficulty in binding between native and recycling LDPE, and achieves the good processing performance of the product and the satisfaction of food safety standards.

CN119816547APending Publication Date: 2025-04-11EQUISTAR CHEMICALS LP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202380062615.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-08
Filing Date
2023-09-07
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The prior art is difficult to effectively combine native low-density polyethylene (LDPE) with post-consumer recycling, resulting in product quality declines or failure to meet safety standards in the food and beverage industry.

Method used

Compound LDPE polymers with a density of 0.915-0.928 g/cm3 and a melt index of 3.0-20 g/10 min were prepared by mixing native LDPE with a high shear index of LDPE with a lower melt index in a twin-screw extruder.

Benefits of technology

Achieve good processing properties of composite plastics and their characteristics suitable for cast film, extrusion coating or extrusion lamination applications, while meeting safety standards in the food and beverage industry.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119816547A_ABST
    Figure CN119816547A_ABST
Patent Text Reader

Abstract

Described herein are combinations of composite native low density polyethylene (native LDPE) and post consumer reclaimed low density polyethylene, linear low density polyethylene, or low density polyethylene and linear low density polyethylene compositions having improved processability and mechanical properties, including methods of making the same, products, and applications in food and non-food packaging.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] Existing related applications

[0002] This application is filed under the Patent Cooperation Treaty and claims priority to U.S. Provisional Application No. 63 / 404,820 filed on September 8, 2022, the entire contents of which are incorporated herein by reference.

[0003] Federally Sponsored Research Statement

[0004] not applicable. Technical Field

[0005] The present invention generally relates to blends of virgin low density polyethylene, linear low density polyethylene and high density polyethylene with post-consumer recycled ("PCR") low density polyethylene, linear low density polyethylene or combinations thereof having improved processing properties and properties, including methods of making the same, products and uses thereof. Background Art

[0006] Low-density polyethylene ("LDPE") is a thermoplastic polymer made from petroleum. The density can range from about 0.91 to about 0.95 g / cm 3 The density is "low" compared to other polyethylenes. These low-density polymers are known for their low-temperature flexibility, toughness, and corrosion resistance, and are meltable and moldable. In addition, low-density polyethylene (LDPE) can be manufactured through specific processes to meet food safety standards and can be used for food packaging and storage, but not all LDPE is food-grade safe.

[0007] "Virgin" plastic refers to plastic that comes from raw materials that have never been used by consumers, that is, non-recycled materials. Due to its high strength and non-toxicity, virgin LDPE is widely used in a variety of applications that require flexibility and impact resistance, including: flexible snack food packaging, cups and packaging paperboard coatings, sugar bags, industrial packaging films, grocery / trash bags, produce packaging bags, squeeze bottles and containers, plastic wrap, six-pack beverage rings, etc.

[0008] Recycled low-density polyethylene (LDPE), including linear LDPE ("LLDPE"), can be used in applications similar to virgin LDPE, including pipes, trash bags, bubble wrap, sheets and films. However, reusable packaging products made from recycled LDPE do not always meet the United States Department of Agriculture (USDA) requirements for direct contact with pharmaceuticals and / or food for human consumption.

[0009] To reduce the manufacture and disposal of plastics, efforts continue to be made to recycle plastics, but recycling processes often result in polymer degradation. Therefore, efforts have also been made to blend virgin plastics with recycled plastics to provide higher quality materials. Unfortunately, blending polymers with different properties can also introduce additional variables in the final product that may be undesirable or may result in a reduction in product quality. Therefore, there is a need in the art to provide a better method and product for combining virgin plastics with recycled plastics.

[0010] The present disclosure provides a method for preparing plastics by blending virgin LDPE and PCR LDPE, including linear LDPE ("LLDPE"), so that the plastics can retain or improve the properties of virgin plastics or post-consumer recycled plastics for intended end uses and are suitable for the food and beverage industry. Summary of the invention

[0011] The present invention provides a composite LDPE polymer, which includes a high melt index virgin LDPE and a recycled LDPE or LLDPE polymer with a lower melt index (MI), or a combination of recycled LDPE and LLDPE. The resulting blend, also known as a composite polymer, has a melt index of 3.0-20 g / 10 min, wherein the melt index is measured at 190° C. and 2.16 kg force, and the density is about 0.91-0.93 g / cm 3 or 0.915-0.928g / cm 3 , and has good processing properties, as well as good properties suitable for cast film, extrusion coating or extrusion lamination applications. In some embodiments, the virgin LDPE may also include a small amount of high-density PE ("HDPE") (virgin and / or recycled) to increase the stiffness of the composite plastic, such as improving the scratch resistance of the final product. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] Figure 1A The average peel strength of exemplary formulations of the compound polymers disclosed herein is shown, and Figure 1B The maximum peel strength for the same formulation is shown. DETAILED DESCRIPTION

[0013] The present disclosure relates to processing or mixing virgin plastic with post-consumer recycled plastic in a processing plant to prepare composite plastic. The plastics can be fed into an extruder individually or in combination after being previously extruded and pelletized. In the extruder, the plastics can be melted and mixed, and then extruded and pelletized for subsequent applications, particularly in cast film, extrusion coating or extrusion lamination layers.

[0014] In one embodiment, the plastics (virgin LDPE and PCR LDPE and / or LLDPE) can be mixed in a single screw extruder. Testing of single screw blending methods has shown that this method may be less preferred where high quality films are required. Compositions prepared by single screw extrusion can produce significant gels in the resulting film. This may be acceptable in some applications, but for high quality films, higher shear compounding methods are preferred.

[0015] In another embodiment, a co-rotating twin-screw extruder or any other high shear method can be used to mix or blend virgin polymers and recycled polymers. In one embodiment of a twin-screw compounding extruder, two intermeshing and co-rotating screws are used, and the screws are mounted on a spline shaft in a closed barrel. Compared with a single-screw extruder, the composite plastics disclosed herein can be mixed more uniformly in a twin-screw extruder, but any sufficiently high shear method, such as a continuous mixer, a Banbury mixer, etc., can also be used. In one embodiment, virgin LDPE and PCR LDPE and / or LLDPE are melt compounded at a specific mechanical energy greater than about 0.15 kW / kg / hr; alternatively, the specific mechanical energy is 0.15 kW / kg / hr to 0.5 kW / kg / hr; and alternatively, the specific mechanical energy is 0.20 kW / kg / hr to 0.4 kW / kg / hr.

[0016] For more detailed information on co-rotating twin-screw extruders for compounding LDPE, see James L. White and Eung K. Kim, Screw Extrusion: Technology and Principles, 2nd ed., Carl Hanser Verlag, Munich 2010; Klemens Kohlgruber and Werner Wiedmann, Co-rotating Twin-Screw Extruders: Fundamentals, Technology, and Applications, Hanser, Munich 2008; Chan I. Chung, Extrusion of Polymers: Theory and Practice, Carl Hanser Verlag, Munich 2000; and Paul Anderson, Mixing and Compounding of Polymers (2nd ed.), ed., Manas-Zloczower, Tadmore, Massachusetts. 2009, Chapter 25, page 947, the entire contents of which are incorporated herein by reference in their entirety for all purposes.

[0017] Cast film, extrusion coating, extrusion lamination and other methods can be used to prepare plastic films, foils, paper, paperboard, scrims, and woven and nonwoven substrates in the food and non-food packaging industry for extrusion coating or extrusion lamination. In one embodiment of the cast film, extrusion coating and extrusion lamination process, the plastic in the form of pellets or granules can be fed through a feed throat into a barrel (or multiple barrels) including a rotating screw, which is attached to advance the plastic pellets to the heated barrel. At a predetermined extrusion temperature set according to the process and the desired plastic output type, the molten plastic can be formed by a combination adapter, where the feed block can form a multilayer structure, which then passes through and leaves a slot-type keyhole (gap of 0.015 to 0.075) extrusion die to form a film. The film is dripped onto a moving substrate (one for extrusion coating and two for extrusion lamination), and the composite polymer is pressed onto the substrate using the pressure of the pressure roller and the cooling roller to adhere the film to the substrate. The substrate can be treated with a variety of pre-treatment methods, such as corona treatment, plasma treatment, primer treatment, ozone treatment and flame treatment. The finished product is wound on a winder and then enters the next processing step. The film thickness can be 0.2 mil (about 0.005mm) to 50 mil (about 1.27mm).

[0018] Specifically, virgin LDPE with a high melt index is blended with suitable post-consumer recycled LDPE and / or LLDPE with a lower melt index to prepare a medium MI, density of about 0.915-0.928 g / cm 3 Blends with improved processing properties. This is achieved by high shear melt mixing of virgin LDPE and PCR LDPE and / or LLDPE in, for example, a twin screw co-extruder (also known as a "single shot" solution). The blends can be used for cast film, extrusion coating or extrusion lamination layers (including multi-layer structures) to balance the total PCR content in the plastic, moisture barrier, material cost and film thickness.

[0019] The melt index of the virgin LDPE of the present disclosure can be greater than 2g / 10min. In another embodiment, its MI is 2-18g / 10min, more preferably 2-10g / 10min or 2-8g / 10min. In contrast, the MI of recycled low-density polyethylene (LDPE) and / or linear low-density polyethylene (LLDPE) is lower, such as 0.50-1.5g / 10min, or about 0.5-0.85g / 10min, or about 0.75-1.25g / 10min, or about 1.0-1.5g / 10min. Depending on the ratio of the two plastics used, composite plastics generally have a medium level of MI. Typically, the ratio of the two components is selected so that the target value of the melt index (MI) of the final blend is 3 to 20g / 10min, or 3 to 11g / 10min, or 8 to 20g / 10min, or about 9 to 15g / 10min.

[0020] The density of the virgin LDPE starting material can be from 0.915 to about 0.932 g / cm 3 In another embodiment, the virgin LDPE starting material of the present disclosure may have a molecular weight of about 0.920 to 0.925 g / cm 3 density.

[0021] The density of the recycled LDPE and / or LLDPE starting material (including combinations thereof) may be from 0.915 to about 0.932 g / cm 3 In another embodiment, the density of the recycled LDPE and / or LLDPE starting material of the present disclosure may be from about 0.920 to 0.925 g / cm 3 The composite polymer may have a density similar to that of the starting materials, or, where the starting materials have different densities, the composite polymer may have a density intermediate between the starting materials.

[0022] In one embodiment, the composite polymer may include at least 15 wt.% recycled LDPE, LLDPE or a combination thereof, preferably at least 20 wt.%, 25 wt.%, 30 wt.%, 35 wt.% or about 40 wt.% recycled LDPE, LLDPE or a combination thereof. Higher amounts may be up to about 85 wt.%, but the cost of PCR LDPE, LLDPE or a combination thereof is currently about 10% higher than virgin LDPE, so 30-40 wt.% or 35 wt.% may be preferred.

[0023] Therefore, composite blends can be used in multilayer film structures to balance the total PCR content in the plastic, material cost and film thickness. Compounding virgin and PCR with different melt indexes can produce a plastic film that can be processed at higher extruder outputs than virgin LDPE.

[0024] The composite plastic and sheets or films made from it can be used in any product typically made from LDPE, including but not limited to: snack food packaging, paper cups, commercial paper beverage cups, ice cream containers, candy packaging, household wrapping paper, tarpaulins, signs, metallized packaging, coffee packaging, dog food bags, etc.

[0025] In other embodiments, the composite plastic can be used for cast film, extrusion coating, and extrusion lamination. To evaluate extrusion coating performance, testing has been completed to compare the processability of the composite PCR resin with standard extrusion coating grades. The samples were evaluated for processability and similar process parameters as standard extrusion coating resin grades were achieved using the PCR composite resin. The process conditions for processability were: melt temperature 623°F, 1000 feet per minute, a coating weight of 0.3 mils, and a total shrinkage of 3.75 inches. These are standard parameters for extrusion coating grades achieved using the PCR composite resin of the present invention.

[0026] The present disclosure includes any one or more of the following embodiments, and any combination thereof:

[0027] A composite polymer comprising: a) 15-85 wt.% of virgin low-density polyethylene (virgin LDPE) having a melt index of 2.0-18.0 g / 10 min; b) 15-85 wt.% of post-consumer recycled low-density polyethylene, linear low-density polyethylene, or a mixture of low-density polyethylene and linear low-density polyethylene (PCR), having a melt index of 0.5-1.5 g / 10 min and a density of 0.915-0.932 g / cm 3 ; c) the melt index of the composite polymer is 3.0-20g / 10min and the density is 0.915-0.923g / cm 3; d) wherein the melt index is measured at 190°C and 2.16 kg load.

[0028] Any of the composite polymers described herein, wherein the composite polymer is mixed at a temperature exceeding 125°C with a specific mechanical energy greater than 0.10 kW / kg / hr. Preferably, the composite polymer is mixed using a twin screw compounding extruder at a temperature of 125°C to 299°C or 150°C to 220°C.

[0029] Any of the composite polymers described herein, wherein the density of the original LDPE is about 0.915-0.932 g / cm 3 , and the density of PCR LDPE and / or LLDPE is about 0.915-0.932g / cm 3 .

[0030] Any of the composite polymers described herein, wherein the composite polymer has a density of about 0.924 g / cm 3 .

[0031] Any composite polymer described herein, wherein the ratio of virgin LDPE to PCR LDPE and / or LLDPE is about 60 / 40, 70 / 30 or 65 / 35.

[0032] Any composite polymer described herein, wherein the virgin LDPE and the PCR LDPE and / or LLDPE are food grade safe, and / or the resulting composite polymer is food grade safe.

[0033] Any composite polymer described herein, the composite polymer comprising 60-70 wt.% of a virgin LDPE having a melt index of about 10 g / 10 min; 30-40 wt.% of a PCR LDPE and / or a PCRL LDPE having a melt index of about 0.5-1.5 g / 10 min; and wherein the melt index of the composite polymer is about 7 g / 10 min and the density is about 0.920-0.930 g / cm 3 or 0.924 g / cm 3 .

[0034] Any composite polymer described herein, the composite polymer comprising: 60-70wt.% of a virgin LDPE having a melt index of about 10 g / 10 min; 30-40wt.% of a PCR LDPE and / or LLDPE having a melt index of about 0.5-1.5 g / 10 min; and wherein the composite polymer is food grade safe and has a melt index of about 7 and a melt index of about 0.920-0.930 g / cm 3 or 0.924 g / cm 3 density.

[0035] A polymer film, coating or laminate made from any of the composite polymers described herein. Preferably, the film, coating or laminate has 90% less gel than a similar polymer composited using a single screw extruder. Preferably, the cast film, extrusion coating or extrusion laminate has a defect count of less than 150 / m for a defect size of 500 mm to 7500 mm. 2 ; For defect sizes from 750mm to 1000mm, the defect count is less than 15 / m 2 ; For defect sizes from 1000mm to 1250mm, the defect count is less than 1.5 / m 2 ; For defect sizes of at least 1250 mm, the defect count is less than 1.5 / m 2 .

[0036] A polymer film, coating or laminate comprising any of the composite polymers herein and having a thickness of less than 10 pounds polymer / ream at a line speed greater than 1,000 feet / minute; and / or a drawdown of less than 8 pounds / ream at a line speed greater than 1,000 feet / minute; and / or a drawdown of less than 5 pounds / ream at a line speed greater than 1,000 feet / minute.

[0037] A polymer film, coating or laminate comprising one or more layers of any composite polymer described herein and having a neck-in of less than 8 inches at a line speed greater than 1,000 feet per minute; and / or a neck-in of less than 6 inches at a line speed greater than 1,000 feet per minute; and / or a neck-in of less than 4 inches at a line speed greater than 1,000 feet per minute.

[0038] As used herein, the term "virgin" refers to unused material provided by the manufacturer.

[0039] As used herein, "PCR" or "post-consumer recycled plastic" refers to plastic that has been converted into products, used by consumers, and subsequently recycled. The PCR used in this disclosure is recycled LDPE, recycled LLDPE, or a combination thereof. Small amounts of recycled HDPE can also be used to improve properties such as stiffness.

[0040] As used herein, the term "composite plastic", "composite polymer" or "polymer blend" refers to a homogeneous mixture comprising virgin LDPE and PCR LDPE and / or LLDPE (including combinations thereof) and possibly other minor additives.

[0041] As used herein, the percentage of virgin LDPE or recycled LDPE and / or LLDPE refers to the weight percentage of the polymer and does not include any minor additives such as colorants, lubricants, etc.

[0042] As used herein, "melt index" ("MI") or "melt flow index" ("MFI") refers to the measurement of the extrusion rate of a molten resin through a standard die (2.095×8 mm) at 190°C and 2.16 kg force according to ASTM D1238-20 (Procedure B). It is defined as the weight of polymer that flows through a standard capillary in 10 minutes at a given temperature under a standard load, in grams. Generally, a plastic with a high melt flow index (MI) indicates that its material viscosity is lower, and the flow characteristics of two plastics can be compared by comparing the melt flow index (MI).

[0043] The thickness of plastic film is usually measured by micrometer ASTM-D6988 or ASTM-D8136. Mil is a common unit for measuring the thickness of plastic film. Thickness is also usually expressed in gauges. A simple conversion relationship is: 1 mil = 100 gauge = 25.4 microns.

[0044] As used herein, "OCS" or "Optical Control System" is a method for determining film quality in which a high-resolution camera takes a picture of the film and gels or defects are identified and quantified. Software is used to classify the gels and output a composite gel count. US7393916 provides an exemplary description of OCS and composite gel counts.

[0045] As used herein, "gel" refers to a defect in a polymer film. A gel is a local defect that is visually distinct from the surrounding film and can be caused by uncomplexed polymer, unreacted catalyst, and the like.

[0046] As used herein, "thinning" or "plastic film thinning" refers to making a thinner plastic film. This is done for a variety of reasons, including sustainability, reducing material costs, or based on application requirements.

[0047] The terms "a" or "an" used in the claims or the specification mean one or more unless the context indicates otherwise.

[0048] The term "about" means the numerical value plus or minus the margin of error in the measurement, or, if no measurement method is specified, plus or minus 10%.

[0049] The term "or" as used in the claims is intended to mean "and / or" unless explicitly indicated to refer to only alternatives or the alternatives are mutually exclusive.

[0050] The terms "comprises," "having," "including," and "containing" (and variations thereof) are open-ended linking verbs that allow for the addition of other elements when used in a claim. The term "consisting of" is closed and excludes all additional elements. The term "consisting essentially of" excludes additional material elements, but allows for the inclusion of non-material elements that do not materially change the disclosure, such as instructions for use, colorants, lubricants, etc. Any claim or claim element introduced with the open transition term "comprising" may be qualified using the expression "consisting essentially of" or "consisting of," and vice versa. However, for the sake of brevity, the entire contents of the claims will not be repeated verbatim herein.

[0051] This article uses the following abbreviations:

[0052]

[0053] The embodiments herein are merely exemplary and do not constitute an excessive limitation on the scope of the appended claims. Although the present disclosure and its advantages have been described in detail, it should be understood that various changes, substitutions and modifications may be made without departing from the scope of the present disclosure defined by the claims.

[0054] Heat sealability and peel strength

[0055] Heat sealing is a critical process associated with product packaging, especially liquid food packaging. The heat sealing properties of an exemplary formulation of the composite polymer described herein were tested and compared with a virgin LDPE sample (purchased from LyondellBasell) without PCR.

[0056] Sample 1 was formulated with 65 wt.% of the same virgin LDPE used in the comparative example and 35 wt.% of PCR LDPE. In this evaluation, the composite PCR resin was processed with the following parameters: melt temperature of 623°F, speed of 1000 fpm, resulting coating weight of 0.3 mils, and total neck-in of 3.75 inches. These are common parameters for LDPE extrusion coating.

[0057] The sealing temperature of LDPE and composite polymer sample 1 on the substrate was changed, and the results are shown in Table 1.

[0058]

[0059] As shown in Table 1, the seal strength of Sample 1 was comparable to that of the virgin resin (Comparative) over the entire temperature range. At temperatures above 216°F, both samples experienced delamination, i.e., seal failure at the interface between the low density polyethylene (LDPE) extrusion layer and the substrate. Therefore, no change in seal strength due to the inclusion of PCR LDPE was observed.

[0060] The peel strength is an indicator used to measure the adhesive strength of two or more materials after bonding. The average peel strength and maximum peel strength of sample 1 were compared with those of the control. Figure 1A and Figure 1B shown.

[0061] like Figure 1A As shown, the peel strength of Sample 1 at all temperatures is higher than that of the comparative example. However, the maximum peel strength of Sample 1 at 225°F is about 2.5 lb / in, which is less than that of the comparative example (3.6 lb / in at 230°F). Regardless, the two samples have similar peel strengths.

[0062] Prospective Example: Film Quality

[0063] The quality of films and coatings of the composite plastics of the present invention will be analyzed using an optical control system (OCS). In the OCS, a high-resolution camera films the extruded composite plastic and gels or defects are identified and quantified. It is expected that the compounded plastics of the present invention compounded using a co-rotating twin-screw extruder will have 50%, 60%, 70% or 85% less gels than similar polymers compounded using a single-screw extruder; for defect sizes between 500mm and 7500mm, the defect count is less than 150 / m 2 ; For defect sizes between 750mm and 1000mm, the defect count is less than 15 / m 2 ; For defect sizes between 1000mm and 1250mm, the defect count is less than 1.5 / m 2 ; For defects with a size of at least 1250 mm, the defect count is less than 1.5 / m 2 ; or any combination of the above.

[0064] The foregoing disclosure describes preferred embodiments of the present disclosure. In view of the description of this specification, various changes and modifications may be proposed by those skilled in the art. For example, additional additives may be added to the above-mentioned compositions to achieve other desired properties of food-grade or non-food-grade compositions. Therefore, such changes and modifications should be considered within the scope of the present disclosure.

[0065] The following references are incorporated herein by reference in their entirety for all purposes.The ASTM standards cited herein were used to determine the properties of the claimed polymers.

[0066] ASTM D256-10 Standard test method for determination of Izod pendulum impact strength of plastics.

[0067] ASTM D638-14 Standard Test Method for Tensile Properties of Plastics.

[0068] ASTM D790-17 Standard test method for flexural properties of unreinforced and reinforced plastics and electrical insulating materials.

[0069] ASTM D792-20 is a standard test method for density and specific gravity (relative density) of plastics by the displacement method.

[0070] ASTM D1238-20 is a standard test method for determining the melt flow rate of thermoplastics using an extrusion plastometer.

[0071] ASTM F1249-20 Standard test method for water vapor transmission rate of plastic film and sheeting using a modulated infrared sensor.

[0072] ASTM D6980-17 Standard Test Method for Determination of Water in Plastics by Weight Loss.

[0073] ASTM D6988-21 Standard Guide for Determination of Thickness of Plastic Film Specimens.

[0074] ASTM D7310-21 Standard Practice for Detection and Rating of Defects in Plastic Films Using Optical Sensors.

[0075] ASTM D8136 is a standard test method for determining the thickness and thickness variability of plastic films using a nontoxic contact capacitance thickness gage.

[0076] US2013015604 Process for making PCR particles.

[0077] US7393916 Method for reducing gels in polyolefins.

[0078] US10124527 Extrusion process of polyethylene polymers.

[0079] US10138310 prepares LLDPE resin and film with low gel.

[0080] Cutzwiler, GW, et al., 'Mixed post-consumer recycled polyolefins asaproperty tuning material for virgin polypropylene.' J.Cleaner Production(2019) 239:117978.doi.org / 10.1016 / j.jclepro.2019.117978.

[0081] McKeen,L.W.,Permeability properties of plastics and elastomers,FourthEd.(2017).

[0082] Albareeki,M.M.;Discoll,S.B.;Barry,C.F.‘Compounding of polyethylenecomposites using high speed twin and quad screw extruders.’AIP Conf.Proc.2139(2019),020006.doi.org / 10.1063 / 1.5121653.

Claims

1. A composite polymer, comprising: a) 15-85 wt.% of virgin low density polyethylene (virgin LDPE) having a melt index of about 2.0-18.0 g / 10 min; b) 15-85 wt.% of post-consumer recycled low-density polyethylene, linear low-density polyethylene, or a combination of low-density polyethylene and linear low-density polyethylene (PCR) having a melt index of about 0.5 g / 10 min to about 1.5 g / 10 min and a density of about 0.915 to about 0.932 g / cm 3 ; c) wherein the composite polymer has a melt index of about 3-20 g / 10 min and a density of about 0.915-0.924 g / cm 3 , d) The melt index is measured at 190°C and 2.16 kg force.

2. The composite polymer according to claim 1, wherein the composite polymer is mixed at a temperature exceeding 125°C with a specific mechanical energy greater than 0.10 kW / kg / hr.

3. The composite polymer according to claim 1, wherein the composite polymer is compounded using a twin-screw composite extruder at a temperature of 125°C to 299°C.

4. The composite polymer according to claim 1, wherein the density of each of the virgin LDPE and the PCR is 0.915-0.932 g / cm 3 , and the density of the composite polymer is about 0.924 g / cm 3 .

5. The composite polymer of claim 1, wherein the ratio of virgin LDPE to PCR is about 65 / 35.

6. The composite polymer according to claim 1, wherein the virgin LDPE and the PCR are food grade safe.

7. The composite polymer according to claim 2, comprising: a) 60 wt.% to 70 wt.% of virgin LDPE having a melt index of about 10 g / 10 min; b) 30 wt.% to 40 wt.% of a PCR having a melt index of about 0.5 g / 10 min to 1.5 g / 10 min; and c) wherein the composite polymer has a melt index of about 7 g / 10 min and a density of about 0.924 g / cm 3 .

8. The composite polymer according to claim 2, comprising: d) 60 wt.% to 70 wt.% of virgin LDPE having a melt index of about 10 g / 10 min; e) 30 wt.% to 40 wt.% of a PCR having a melt index of about 0.5 g / 10 min to 1.5 g / 10 min; and a) The composite polymer is food grade safe, has a melt index of about 7, and a density of about 0.924 g / cm 3 .

9. A polymer film, coating or laminate comprising the composite polymer of claim 3, wherein the film, coating or laminate has 85% less gel than a similar polymer composited using a single screw extruder.

10. The film, coating or laminate of claim 9, wherein the film, coating or laminate has a defect count of less than 150 / m for defect sizes between 500 mm and 7500 mm. 2 .

11. The film, coating or laminate of claim 9, wherein the film, coating or laminate has a defect count of less than 15 / m for defect sizes between 750 mm and 1000 mm. 2 .

12. The film, coating or laminate of claim 9, wherein the film, coating or laminate has a defect count of less than 1.5 / m for defect sizes between 1000 mm and 1250 mm. 2 .

13. The film, coating or laminate of claim 9, wherein the film, coating or laminate has a defect count of less than 1.5 defects / m for a defect size of at least 1250 mm. 2 .

14. A film, coating or laminate comprising one or more layers of the composite polymer of claim 3 having a thickness of less than 10 pounds of polymer per ream and a line speed greater than 1,000 feet per minute.

15. The film, coating or laminate of claim 14 wherein the draft is less than 8 lbs / ream at a line speed greater than 1,000 ft / min.

16. The film, coating or laminate of claim 14, wherein the film, coating or laminate has a defect count of less than 1.5 defects / m for defects greater than or equal to 1500 mm in size. 2 .

17. A film, coating or laminate comprising one or more layers of the composite polymer of claim 3 having a neck-in of less than 8 inches at a line speed greater than 1,000 feet per minute.

18. The film, coating or laminate of claim 17 wherein the neck-in is less than 6 inches at a line speed greater than 1,000 feet per minute.

19. The film, coating or laminate of claim 17 wherein the neck-in is less than 4 inches at a line speed greater than 1,000 feet per minute.

20. The film, coating or laminate of claim 17, wherein the film, coating or laminate has a defect count of less than 1.5 defects / m for defects greater than or equal to 1500 mm. 2 .

Citation Information

Patent Citations

  • Extrusion process for polyethylene polymers

    US10124527B2

  • Preparation of LLDPE resins and films having low gels

    US10138310B2

  • Process of Producing PCR Pellets

    US20130015604A1

  • Method of reducing gels in polyolefins

    US7393916B2